2011
DOI: 10.1111/j.1742-481x.2011.00845.x
|View full text |Cite
|
Sign up to set email alerts
|

The challenges of managing complex lymphoedema/chronic oedema in the UK and Canada

Abstract: This article explores the professional challenges of treating patients with complex/severe forms of chronic oedema/lymphoedema with compression therapy. Four focus groups were held, two in the UK and two in Canada, to examine the challenges faced by practitioners in their everyday practice. A number of challenges were identified by participants in both countries and include the changing profile of lymphoedema/chronic oedema and how increasing complexity is outpacing the development of services and research-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 21 publications
0
16
0
2
Order By: Relevance
“…, Morgan et al . ). The Welsh Government has had devolved responsibility for health care and policy since 1999.…”
Section: Introductionmentioning
confidence: 97%
“…, Morgan et al . ). The Welsh Government has had devolved responsibility for health care and policy since 1999.…”
Section: Introductionmentioning
confidence: 97%
“…Another component of essential care is dietary advice, weight management and wellness. Lymphoedema is a chronic condition with associated chronic illness challenges (Hardy, 2006;Morgan et al, 2012), and patients require form a tourniquet around the toes due to movement of bandages causing skin damage, and is often omitted due to the need for daily reapplication, which in turn results in fluid being pushed into the toes (Todd, 2011). The introduction of toe gloves has reduced the risk of tissue damage caused through toe bandaging and has achieved greater concordance from patients as garments are more comfortable and less likely to cause trauma.…”
Section: Health and Wellbeingmentioning
confidence: 99%
“…Furthermore, the application of compression to obese limbs with an altered shape obviously proves difficult. It has been reported that up to 75% of patients attending a specific specialist service were obese, demonstrating a need for specialist equipment and a need to increase pressure on budgets (Morgan et al, 2012;Moffatt, 2014).…”
Section: Other Essential Carementioning
confidence: 99%
“…Chronic edema is a major clinical problem that impacts on an individual’s physical and psychosocial wellbeing [9, 11, 12]. Unmanaged CO predisposes the individuals to leg ulcers/wounds, recurrent cellulitis and possibly hospitalization [3, 11, 13].…”
Section: Introductionmentioning
confidence: 99%